2019
DOI: 10.1111/jfbc.13118
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the antioxidant intensities of seven different soybean ( Glycine max (L.) Merr.) cultivars during drought

Abstract: Drought stress-induced antioxidative defense responses were studied in seven soybean (Glycine max (L) Merr.) cultivars PUSA 9712, LSB 1, JS 335, ADB 22, NRC 37, DSB 20, and MAUS 61, respectively. Drought stress was imposed by withholding irrigation till the leaf water potentials reached −1.0, −1.5, and −2.0 MPa. Lipid peroxidation and superoxide, H 2 O 2 , • OH, DPPH radical scavenging assays were performed. Antioxidants during drought stress were studied by quantifying the ascorbic acid, glutathione, α-tocoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It is also hypothesized that H 2 O 2 is likely to play a key role in preventing biotic stressor-induced infections [ 61 ]. As a result of the previous effects, the gene expression level of the ascorbate peroxidase (APX) enzyme also increased, which can also indirectly explain the quantitative increase in H 2 O 2 production [ 62 ]. In plants, APXs can neutralize the accumulated H 2 O 2 by converting it to water [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also hypothesized that H 2 O 2 is likely to play a key role in preventing biotic stressor-induced infections [ 61 ]. As a result of the previous effects, the gene expression level of the ascorbate peroxidase (APX) enzyme also increased, which can also indirectly explain the quantitative increase in H 2 O 2 production [ 62 ]. In plants, APXs can neutralize the accumulated H 2 O 2 by converting it to water [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…, 2018). The ASC and GSH cycle system is one of the keys in the process of ROS scavenging (Easwar Rao and Viswanatha Chaitanya, 2020). To determine whether the molecules responsible for ROS scavenging are depleted when ROS concentration in the nucleus is overexpressed, the oxidation levels of ASC‐GSH and lipids in the cells were measured (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…However, flavonoids, including rutin, are stressful substances, and prolonged stress does not necessarily enable continued flavonoid accumulation ( 57 ). The antioxidant levels in soybean during drought showed an alternating increasing and decreasing trend, suggesting that short-term drought could rapidly enhance antioxidant intensities, while long-term droughts might cause plants to gradually adapt to these stresses and stop enhancement ( 58 ). Also, plant antioxidant enzyme activities showed a similar trend under abiotic stress, which revealed that short-term stress could increase plants' secondary metabolite production, while secondary metabolites under long-term stress might return to a lower level ( 59 ).…”
Section: Discussionmentioning
confidence: 99%